PENGARUH PEMEKARAN TERHADAP PEMBANGUNAN (KAJIAN PEMEKARAN DI KALIMANTAN TIMUR ) - Florentinus Sudiran (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
This  research is held in East Kalimantan during the year of 2012 to 2014 .The method of the research is kualitatif one.The collection of the data is taken from the library ,and news paper.The theory of the dependent and independent variables taken from literature  such as books in the library of the University of 17 Agustus 1945 Samarinda and others.The news was taken from newspapers Tribun Kaltim and Kaltimpost.The result of the research is that most of the DOB in East Kalimantan is succesful in managing the government.Especially for the South-East Kalimantan as the pormising DOB (new area autonomy)  is still in the discusssion because there are many arguments whether people agreee or disagree .Some who agree they say that its better to make DOB (new area autonomy)  South-East Kalimantan to encourage the area to develop.On the other hand who do not agree to have DOB  South-East Kalimantan it is imposible to do because the resource of the area is very limited.